A Japanese Herbal Formula, Daikenchuto, Alleviates Experimental Colitis by Reshaping Microbial Profiles and Enhancing Group 3 Innate Lymphoid Cells - Shi, Zhengzheng; Takeuchi, Tadashi; Nakanishi, Yumiko; Kato, Tamotsu; Beck, Katharina; Nagata, Ritsu; Kageyama, Tomoko; Ito, Ayumi; Ohno, Hiroshi; Satoh-Takayama, Naoko (Frontiers in Immunology, 2022)
Daikenchuto (DKT) is one of the most widely used Japanese herbal formulae for various gastrointestinal disorders. It consists of Zanthoxylum fructus (Japanese pepper), Zingiberis Siccatum Rhizoma (processed ginger), Ginseng radix, and maltose powder. However, the use of DKT in clinical settings is still controversial due to the limited molecular evidence and largely unknown therapeutic effects. Here, we investigated the anti-inflammatory actions of DKT in the dextran sodium sulfate (DSS)-induced colitis model in mice. We observed that DKT remarkably attenuated the severity of experimental colitis while maintaining the members of the symbiotic microbiota such as family Lactobacillaceae and increasing levels of propionate, an immunomodulatory microbial metabolite, in the colon. DKT also protected colonic epithelial integrity by upregulating the fucosyltransferase gene Fut2 and the antimicrobial peptide gene Reg3g. More remarkably, DKT restored the reduced colonic group 3 innate lymphoid cells (ILC3s), mainly RORgammathigh-ILC3s, in DSS-induced colitis. We further demonstrated that ILC3-deficient mice showed increased mortality during experimental colitis, suggesting that ILC3s play a protective function on colonic inflammation. These findings demonstrate that DKT possesses anti-inflammatory activity, partly via ILC3 function, to maintain the colonic microenvironment. Our study also provides insights into the molecular basis of herbal medicine effects, promotes more profound mechanistic studies towards herbal formulae and contributes to future drug development.